Spatio Temporal Analysis of Covid-19 Cases Distribution Pattern in Batang Regency - Isniyati, Heni; Nurjazuli, Nurjazuli; Setiani, Onny (International Journal of English Literature and Social Sciences (IJELS), 2021)
The Covid-19 cases increase significantly in Batang Regency since it was first identified on April 4, 2020 until nowadays. The efforts and strategies have taken by the government to reduce the rate of Covid-19, but have not shown significant results. There has increased 1.125 cases in Batang Regency on December 2020. This study aimed was analyzed by spatio temporal approach of the Covid-19 case and determine the distribution pattern of the Covid-19 in Batang Regency. Methods: This type of research was an observational research with a spatiotemporal explanatory research design. Data analysis for spatial autocorrelation were performed using Moran's index and location quotient (LQ) index. The research data were obtained from the Batang Regency Health Office. The sample in this study were 248 villages in Batang Regency.Result and discussion:The results showed that as many as 209 villages (84.3%) were identified cases , and 39 villages (15.7%) had no identified cases of the Covid-19. The results of the moran’s index showed that the pattern of the Covid-19 incidence which has a significant spatial correlation in 248 villages with p value <0.01 and Z-score> 2.58. The results of the Location Quotient (LQ) index shows that 78 villages (31.4%) in Batang Regency having high level of the Covid-19 concentration (LQ> 1). Conclusion: The distribution pattern of Covid-19 shows a change in pattern from random to clustered. Spatio-temporal analysis of Covid-19 cases shows an increase in the number and areas of cases.